2015
DOI: 10.1016/j.mee.2015.03.028
|View full text |Cite
|
Sign up to set email alerts
|

The static and dynamic response of SU-8 electrothermal microgrippers of varying thickness

Abstract: Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in the Journal of microelectronic engineering. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be re ected in this document. Changes may have been made to this work since it was submitted for publication. A de nitive version was subsequently published in the Journal of microelectronic engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In other words, large output forces can be produced by applying relatively low voltages (below 10 V) [13,14]. Electrothermal actuators have been widely deployed for microgripping applications [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In other words, large output forces can be produced by applying relatively low voltages (below 10 V) [13,14]. Electrothermal actuators have been widely deployed for microgripping applications [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…They include actuators and gripping arms made of thin silicon or stainless sheets, which are used to produce sufficient strength. Several research studies have reported on the design and performance analysis of microgrippers [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The design aspects of these microstructures include the kinematic structure [18,24], the material selection [21,24], the actuation mechanism [16], the fabrication process [17,20], and the impact of the surrounding environment on their operation [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations